Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fneur.2018.00878
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence of Sex Differences in Cortical Thickness Following Acute Mild Traumatic Brain Injury

Abstract: The main objective of this study was to evaluate sex differences in cortical thickness after acute mild traumatic brain injury (mTBI) and its associations with clinical outcomes. Thirty-two patients with mTBI at acute phase (2.4 ± 1.3 days post-injury) and 30 healthy controls were enrolled. All the participants underwent comprehensive neurocognitive assessments and MRI to assess cortical thickness. Significant sex differences were determined by using variance analysis of factorial design. Relations between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Specifically, one study showed that after mTBI, male (compared with female) patients had significantly increased connectivity in the ventral stream network known to play an integral role in visual processing; another study linked increased thickness of the left caudal anterior cingulate cortex to increased Symptom scores in female patients compared with male patients after mTBI. 43,48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, one study showed that after mTBI, male (compared with female) patients had significantly increased connectivity in the ventral stream network known to play an integral role in visual processing; another study linked increased thickness of the left caudal anterior cingulate cortex to increased Symptom scores in female patients compared with male patients after mTBI. 43,48…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, one study showed that after mTBI, male (compared with female) patients had significantly increased connectivity in the ventral stream network known to play an integral role in visual processing; another study linked increased thickness of the left caudal anterior cingulate cortex to increased Symptom scores in female patients compared with male patients after mTBI. 43,48 Previous studies have examined symptom cluster discrepancies between the sexes in amateur athletes both at baseline and after concussion. 12,13,16,39,50 Although these studies agree that female athletes experience more symptoms than male athletes, the specific clusters that differ between the sexes has been inconsistent, due in part to inconsistent methods.…”
Section: Severity Indexmentioning
confidence: 99%
“…All of the mTBI patients in this cohort study were enrolled from the Department of Radiology of the Second Xiangya Hospital between September and December 2019. The sample size calculation was based on previous studies (Zhou et al, 2013;Shao et al, 2018;Ofoghi et al, 2020). The mTBI patients were pre-screened prior to scanning to rule out any contraindications to MRI.…”
Section: Participantsmentioning
confidence: 99%
“…The inclusion criteria for the mTBI patients were based on the World Health Organization's Collaborating Center for Neurotrauma Task Force (Holm et al, 2005): (1) Glasgow Coma Scale (Teasdale et al, 2014) score ranging from 13-15; (2) one or more of any of the following: (a) existence of confusion or disorientation, (b) loss of consciousness of less than 30 minutes, (c) post-traumatic amnesia of less than 24 hours, (d) existence of transient neurologic abnormalities (focal signs or seizure), (e) existence of an intracranial lesion not requiring surgery; (3) mTBI onset within 7 days of trauma. The exclusion criteria for mTBI patients followed those used in the study of Shao et al (2018):…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation